Nuove specie di Lomechusini mirmecofili e non mirmecofili dell’ Amazzonia (Coleoptera, Staphylinidae). - Pace, Roberto (Contributions to Entomology = Beiträge zur Entomologie, 2008)
Six species of Lomechusini of the genus Apalonia Casey from the Amazon Valley are described and illustrated: Apalonia izzoi n. sp., A. globulifera n. sp., A. terminalis n. sp., A. hemisphaerica n. sp., A. latissima n. sp., and A. myrmecobia n. sp. These species prey on Crematogaster ants just when they are defending it selves against Pseudacteon Phorids (Diptera). The genus Manausdota n. gen. of the Lomechusini is described and illustrated (type species Manausdota amazonica n. sp.). It is similar to the genera Apalonia Casey and Parapycnota Bernhauer and includes two species: Manausdota amazonica n. sp. and M. cavicollis n. sp. Sommario Sono descritte e illustrate sei specie di Lomechusini del genere Apalonia Casey dell’Amazzonia: Apalonia izzoi n. sp., A globulifera. n. sp., A. terminalis n. sp., A. hemisphaerica n. sp., A. latissima n. sp., A. myrmecobia n. sp. Queste specie sono predatrici solamente di formiche Crematogaster quando stanno difendendosi dal Foride Pseudacteon (Diptera). Il genere Manausdota dei Lomechusini è descritto ed illustrato come nuovo per la scienza per una nuova specie: M. amazonica. È simile ai generi Apalonia e Parapycnota Bernhauer e comprende due specie: Manausdota amazonica n. sp. e M. cavicollis n. sp. Keywords Coleoptera, Staphylinidae, Aleocharinae, new genus, new species, taxonomy, myrmecophyly, South America. Nomenclatural Acts globulifera Pace, 2008 (Apalonia), spec. n. hemisphaerica Pace, 2008 (Apalonia), spec. n. izzoi Pace, 2008 (Apalonia), spec. n. latissima Pace, 2008 (Apalonia), spec. n. myrmecobia Pace, 2008 (Apalonia), spec. n. terminalis Pace, 2008 (Apalonia), spec. n. amazonica Pace, 2008 (Manausdota), spec. n. cavicollis Pace, 2008 (Manausdota), spec. n. Manausdota Pace, 2008 (Staphylinidae), gen. n.